Peranan E-Lit (Elektronik Literasi) Sebagai Perpustakaan Online Guna Meningkatkan Minat Baca Peserta Didik SMK Yarsi Mataram - Febina, Ruyati; Khaerunisah, Khaerunisah; Oktaria, Soraya (Jurnal Pengabdian Masyarakat Sains Indonesia (Indonesian Journal Of Science Community Services), 2023)
Media that can increase reading literacy include books, magazines, newspapers, as well as online media, one of which is the online library. E-Lit (Electronic Literacy) is an online library containing school textbooks and fiction books. This E-Lit is created in Google Drive so it can be used with digital devices such as smartphones, laptops and computers. The aim of this research is to determine the role of E-Lit (Electronic Literacy) in increasing students' interest in reading at SMK Yarsi Mataram. This research method is a quantitative method with a descriptive approach. The data taken is primary data related to the topic of discussion including; interest in reading, E-Lit Media, and SMK Yarsi Mataram Students. Data was obtained from a questionnaire filled out by students at SMK Yarsi Mataram as the data source for this research. The advantages of using E-Lit are (1) Long Distance Service; (2) Easy access; (3) Cheap; (4) Digital collection maintenance; (5) Global network. Meanwhile, the weakness in accessing E-Lit is that user must have an adequate internet network and use an internet quota or Wi-Fi. So it can be concluded that E-Lit media plays an important role in increasing reading literacy in SMK Yarsi Mataram. Because it can increase students' enthusiasm and interest in reading. Apart from that, it can make it easier for students and teachers in the teaching and learning process.